Growth and Forage Quality Responses of Smooth Bromegrass to Nitrogen Placement and Timing. (1st November 2016) - Moyer, Joseph; Sweeney, Daniel
Abstract : Smooth bromegrass [ Bromus inermis (L.)] is a cool‐season perennial that is widely used in pastures and meadows. More intensive management of N may be required to optimize production. This study was conducted for 4 yr to determine bromegrass dry forage mass (FM) and quality responses to annual rates of 84 or 168 kg ha −1 of N fertilizer solution with three placements at four different fall/late winter (LW) timing combinations. Vegetative forage was harvested in April to represent early grazing, or postanthesis, in May to simulate hay production. Knife (KN) placement generally resulted in less vegetative FM than broadcast (BC) and dribble (DR) placements, regardless of N rate. In two typical moisture years, FM increased an average 15% when N rate increased from 84 to 168 kg N ha −1, but the first 84 kg ha −1 did not increase yields above the check (0 N). Forage crude protein (CP) generally increased as N rate increased, particularly with KN placement, or when most was applied in LW. Nitrogen increased postanthesis FM by an average of 24% with the first 84 kg ha −1 increment, and by an additional 15% with the next 84‐kg increment, while average CP was increased by 20%. Knife placement increased mass and CP, particularly with the 168 kg ha −1 rate, and when some was applied in LW, but often with increased neutral detergent fiber and decreased digestible dry matter. The most beneficial N management system would be determined by the projected forage use. Core Ideas Nitrogen fertility management of smooth bromegrass affects not only yield, but forage quality. Placement of N fertilizer affects bromegrass yield and quality. Responses to N amount and placement are also modified by application timing.